2005
DOI: 10.1111/j.1365-2966.2005.08855.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and kinematics of edge-on galaxy discs - V. The dynamics of stellar discs

Abstract: In earlier papers in this series we determined the intrinsic stellar disc kinematics of 15 intermediate‐ to late‐type edge‐on spiral galaxies using a dynamical modelling technique. The sample covers a substantial range in maximum rotation velocity and deprojected face‐on surface brightness, and contains seven spirals with either a boxy or peanut‐shaped bulge. Here we discuss the structural, kinematical and dynamical properties. From the photometry we find that intrinsically more flattened discs tend to have a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
102
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 80 publications
(148 reference statements)
23
102
1
1
Order By: Relevance
“…On average, after rejecting UGC 1862 which has no measurement of V c at 2.2h R , F 2.2h R b =0.57±0.07 (std). This result is consistent with what was found by Bottema (1993) and Kregel et al (2005), and based on the correlations with M K and μ i 0,K seen in Fig. 14, we conclude that small differences in the mean may be due to differences in the galaxy samples. However, also note that both Bottema (1993) and Kregel et al (2005) measured the disk mass fraction, excluding the contribution from the stellar bulge (see discussion in Sect.…”
Section: The Dynamical Importance Of the Baryonssupporting
confidence: 81%
See 3 more Smart Citations
“…On average, after rejecting UGC 1862 which has no measurement of V c at 2.2h R , F 2.2h R b =0.57±0.07 (std). This result is consistent with what was found by Bottema (1993) and Kregel et al (2005), and based on the correlations with M K and μ i 0,K seen in Fig. 14, we conclude that small differences in the mean may be due to differences in the galaxy samples. However, also note that both Bottema (1993) and Kregel et al (2005) measured the disk mass fraction, excluding the contribution from the stellar bulge (see discussion in Sect.…”
Section: The Dynamical Importance Of the Baryonssupporting
confidence: 81%
“…Bottema (1993) found that disks contribute only 63 ± 10% to the observed rotation speed. Kregel et al (2005) found an even smaller average disk contribution of 58 ± 5%, with a 1σ scatter of 18% when including two outliers. Excluding the outliers, they find an average disk contribution of 53 ± 4%, with a 1σ scatter of 15%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to determine a disk mass from a measured vertical velocity dispersion in a face-on system we have to make assumptions about the (unobservable) vertical stellar distribution, while for edge-on systems, where we can measure the vertical stellar distribution, we have to relate the observed radial and tangential velocity dispersion to the (unobservable) vertical velocity dispersion (Bottema 1997). Recently, Kregel et al (2005) used velocity dispersions of a sample of 15 edge-on galaxies to determine a dynamical mass Tully-Fisher relation and compared it to the stellar population mass Tully-Fisher relation of Bell & de Jong (2001). They find an offset of about -0.24 dex, assuming a vertical-to-radial velocity dispersion ratio (σ z /σ R ) of 0.6.…”
Section: Disk Velocity Dispersionsmentioning
confidence: 99%